EFISIENSI PRODUKSI SUSU SAPI PERAH DARA DAN LAKTASI AKIBAT PENYUNTIKAN PMSG - B. Utomo; Subiharta Subiharta; Ramelan Ramelan; Sudjatmogo Sudjatmogo (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2004)
The aim of the presentexperiment was to evaluate the influence of I 500 TU injection of Pregnant Mare Serum Gonadotrophin (PMSG) at the mating program in the Fresian Holstein (FH) dairy cow on the performancesof milk production, quality, and production efficiency. The experimentwas performed at Banaran Village, Cepogo Subdistrict ofBoyolali District used twelve heifers and the-pregnant first parity cow of about 350-450 kg body weight. A split-plot experimental design with heifer (Pol and first parity (P1) as a main plot, and PMSG doses (T0 and T ,)as a sub plot. Thus the treatmentwere I) heifer with no PSMG injection (P0T0), 2) PMSG injected heifer (P0T,), 3) first parity cow with no PMSG injection, and4) PMSG injected first parity cow P,T,). Measurements were conducted on 90 days milk production, mass weight of milk, fat and lactose contents, and milk production efficiency. Results showed that average milk productions of not injected (804.67 l) and injected PMSG heifers ( 1,286.92 l) were significantly different (P<0.05). However, injection of PMSGdid not significantly (P>0.05) influenced average milk productions of first parity cows ( J.0491 versus 1,4832.52 J, for not injected and injected PMSG cow, respectively). Fat production of the not injected and injected PMSG heifers were 25.27 and 41.12 kg (P<0.05), while not injected and injected PMSG first parity cow produced 34. 19 and 47 .0 I kg of fat, respectively (P<0.05). Lactose production of not injected and injected PMSG heifers were 39.11 kg versus60.70 kg (P>0.05). Milk production efficiency of not injected and injected PMSG heifers were 11.13 and 18.45%, respectively (P<0.05). whereas, not injected and injected PMSG first parity cow were 14.75 and I 8.6 % (P>0.05). In general there were no significant differenton theeffectof PMSG injection on milk quality components (mass weight, fat and lactose contents). In conclusion, in the present experiment PMSG injection improved milk pro• duction and it efficiency, but did not improved milk quality.